Acute kidney injury in pregnancy - Taber-Hight, Elizabeth (Adv Chronic Kidney Dis, 2020)
Acute kidney injury (AKI) in pregnancy is a public health problem and a significant cause of maternal and fetal morbidity and mortality. Pregnancy-related AKI is associated with worsening of kidney function resulting in chronic kidney disease and end-stage kidney disease, increased risk of adverse cardiovascular events, higher health care utilization, and longer hospital and intensive care unit stays. The incidence of pregnancy-related AKI has increased in the developed countries, theorized to be the result of an increase in pregnancies in advanced maternal age, and continues to remain higher in developing countries due to inadequate antenatal care and higher frequency of septic abortions. Causes of pregnancy-related AKI can be classified by pregnancy trimester. While hyperemesis gravidarum is a common cause of pregnancy-related AKI during the first trimester; complications like preeclampsia, preeclampsia, hemolysis, elevated liver enzymes, low platelet count (HELLP) syndrome, acute fatty liver disease of pregnancy, thrombotic thrombocytopenic purpura, and hemolytic uremic syndrome are important causes of AKI later in the pregnancy. Diagnosis of pregnancy-related AKI can be difficult due to lack of diagnostic criteria and overlapping clinical features between various causes. Kidney biopsy should be considered when the laboratory evaluation for AKI is non-diagnostic, and a definitive diagnosis will help to facilitate appropriate treatment outweighing the risks of biopsy. Management of AKI in pregnancy should be done by a multidisciplinary team consisting of nephrologists, obstetricians, and neonatologists to ensure best possible maternal and fetal outcomes. General measures to treat pregnancy-related AKI include identification of the underlying cause of kidney injury, intravenous fluid resuscitation, timely initiation of dialysis if needed, and prompt fetal delivery, if necessary. Specific treatment includes steroid and immunosuppressive therapy for glomerulonephritis, prompt delivery for severe preeclampsia, HELLP syndrome and acute fatty liver of pregnancy, and plasmapheresis and eculizumab for thrombotic microangiopathies like thrombotic thrombocytopenic purpura, and atypical hemolytic uremic syndrome. In this review, we discuss the various causes of AKI in pregnancy, diagnostic approaches, complications, and the specific treatment strategies of pregnancy-related AKI.